Computational study of Curcuma zanthorrhiza Roxb compounds as potential antidiabetic towards alpha-amylase, alpha-glucosidase, and Keap1 inhibition - Sasangka Prasetyawan; Anna Safitri; Sri Rahayu (GarVal Editorial Ltda., 2022)
Context: Curcuma zanthorrhiza Roxb is traditionally used as a medicinal herb that is believed might cure some diseases. However, there is still a lack of information about the underlying mechanism of bioactive compounds from C. zanthorrhiza, which has antidiabetic properties. Aims: To analyze the bioactive compounds of C. zanthorrhiza as inhibitors of alpha-amylase, alpha-glucosidase, and Keap1, which play a significant role in diabetes mellitus (DM) progression. Methods: The bioactive compounds of C. zanthorrhiza were screened its antidiabetic activity by PASS server. To determine the interaction between selected active compounds of C. zanthorrhiza, molecular docking was performed by PyRx 0.8 software and visualized in Biovia Discovery Studio and PyMol, respectively. The pharmacological properties of selected active compounds of C. zanthorrhiza were then evaluated using the Lipinski rule and SwissADME. Results: There were 20 from 60 bioactive compounds of C. zanthorrhiza, which have antidiabetic properties. The molecular docking analysis revealed that five from 20 bioactive compounds might be inhibiting alpha-amylase, alpha-glucosidase, and Keap1. Curcumin might be potential as an alpha-amylase, alpha-glucosidase, and Keap1 inhibitor. Curcumin and xanthorrizol were the compounds that meet pharmacological properties criteria. Conclusions: The data suggested that C. zanthorriza compounds may be a promising inhibitor candidate of three key target proteins that have been highly involved in DM. Further research is needed to validate the in vitro and in vivo activity of the C. zanthorrhiza compounds or be used as a primary compound for target DM progression.